2019
DOI: 10.3390/app9163358
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin and Electrically Tunable Metamaterial with Nearly Perfect Absorption in Mid-Infrared

Abstract: Metamaterials integrated with graphene exhibit tremendous freedom in tailoring their optical properties, particularly in the infrared region, and are desired for a wide range of applications, such as thermal imaging, cloaking, and biosensing. In this article, we numerically and experimentally demonstrate an ultrathin (total thickness < λ 0 / 15 ) and electrically tunable mid-infrared perfect absorber based on metal–insulator–metal (MIM) structured metamaterials. The Q-values of the absorber can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In recent years, scholars have proposed various measures to improve the absorption of graphene in the visible and near-infrared range, commonly by coupling graphene with some resonance structures [30][31][32]. For instance, a polarization-dependent graphene absorber with a one-dimensional, sub-wavelength dielectric grating has been theoretically proved to be capable of attaining perfect absorption [33].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, scholars have proposed various measures to improve the absorption of graphene in the visible and near-infrared range, commonly by coupling graphene with some resonance structures [30][31][32]. For instance, a polarization-dependent graphene absorber with a one-dimensional, sub-wavelength dielectric grating has been theoretically proved to be capable of attaining perfect absorption [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, the resonant properties of MPAs are almost fixed, which greatly reduce their practical applications. Therefore, to fully exploit the optical properties and to extend the functionality of MPAs, dynamically tunable control over resonances such as electrical [26], optical [27], and thermal [28] tuning have been studied to realize actively tunable metamaterials. Recently, the thermal tunable narrowband MPAs are emerging with possible applications such as optical modulator [29], optical switches [30], and infrared (IR) camouflage [31].…”
Section: Introductionmentioning
confidence: 99%
“…An analytical expression of the relectance coefficient was derived and showed that minimisation of reflectance is achieved by control of the intrinsic and radiative losses [8]. The ratio of the quality factors of absorption Q a and radiation Q r losses define the minimum of the achievable reflectivity r = (Q a /Q r − 1)/(Q a /Q r + 1), hence the maximum absorbance achievable by MIM structures at Q a /Q r → 1 [9]. With a MIM reflector placed on a nano-thin and flexible Si 3 N 4 -membrane with an electrically biased graphene layer, spectral tunability of the resonance wavelength of the perfect absorber at mid-IR wavelengths was recently demonstrated [9].…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of the quality factors of absorption Q a and radiation Q r losses define the minimum of the achievable reflectivity r = (Q a /Q r − 1)/(Q a /Q r + 1), hence the maximum absorbance achievable by MIM structures at Q a /Q r → 1 [9]. With a MIM reflector placed on a nano-thin and flexible Si 3 N 4 -membrane with an electrically biased graphene layer, spectral tunability of the resonance wavelength of the perfect absorber at mid-IR wavelengths was recently demonstrated [9]. Simple nano-disk MIM surfaces ( Figure 1) showed a near perfect absprbance A = 99% at 1.6 µm wavelengths with high refractive index sensitivity close to the resonance [10].…”
Section: Introductionmentioning
confidence: 99%